2023
DOI: 10.1021/acsmaterialsau.3c00072
|View full text |Cite
|
Sign up to set email alerts
|

2D MOFs and Zeolites for Composite Membrane and Gas Separation Applications: A Brief Review

Minsu Kim,
Wooyoung Choi,
Choong Hoo Lee
et al.

Abstract: Commercial membranes have predominantly been fabricated from polymers due to their economic viability and processability. This choice offers significant advantages in energy efficiency, cost-effectiveness, and operational simplicity compared to conventional separation techniques like distillation. However, polymeric membranes inherently exhibit a trade-off between their permeability and selectivity, which is summarized in the Robeson upper bound. To potentially surpass these limitations, mixed-matrix membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Compared to 1D nanofibers and 3D nanoparticles, adding 2D nanosheets into polymeric matrixes has been proved to be more effective as much less additives but enhancing the gas separation performance significantly . Similar to other representative 2D materials, e.g., graphene, GO and MXene, great efforts have also been dedicated to developing 2D zeolites in recent years . Both top-down exfoliation and bottom-up synthesis methods have been developed for 2D zeolite .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to 1D nanofibers and 3D nanoparticles, adding 2D nanosheets into polymeric matrixes has been proved to be more effective as much less additives but enhancing the gas separation performance significantly . Similar to other representative 2D materials, e.g., graphene, GO and MXene, great efforts have also been dedicated to developing 2D zeolites in recent years . Both top-down exfoliation and bottom-up synthesis methods have been developed for 2D zeolite .…”
Section: Introductionmentioning
confidence: 99%
“…Applying zeolites, such as Si-CHA, SAPO-34, and SSZ-13, as nanofillers in MMMs for CH 4 purification has also been reported over a long time . Specifically, MFI-like zeolites, which have sinusoidal pores in the a -axis and c -axis, as well as one-dimensional straight pores in the b -axis, is favorable for gas diffusion. , Coupled with their large surface area, MFI zeolites have been considered as promising nanofillers in MMMs. A molecular simulation and Monte Carlo study demonstrated that adding MFI nanofillers into polymeric matrixes can greatly improve their CO 2 /CH 4 separation performance …”
Section: Introductionmentioning
confidence: 99%